ANALISIS DAMPAK PROGRAM BEDAH RUMAH TERHADAP KESEJAHTERAAN MASYARAKAT DAN PENGENTASAN KEMISKINAN DI KECAMATAN TEJAKULA BULELENG - Arnawa, I Gede Wirya Krishna; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 12 (2020): VOL 9 NO 12, DESEMBER 2020 (2618-2851), 2020)
Poverty is a condition where a lack or inability to meet the needs of life economically in society. To reduce the amount of poverty, government provides various social assistance for the community, namely house renovation program. House renovation program is an activity carried out in the context of repairing houses that are unfit for habitation, namely houses that do not meet health, security and social requirements. Purpose this study to analyze: 1) welfare of the community after receiving house renovation assistance. 2) The total population taken was 250 with the number of samples taken, namely 71 households receiving the house renovation program.The analytical tool in this research is non-parametric statistics with the Mc Nemar method. The results in this study indicate 1) house renovation program has a significant impact on the welfare of the community in Tejakula District, Buleleng Regency. 2) house renovation program had a significant impact on poverty alleviation in Tejakula District. Based on the research results that have been obtained, the average welfare of the community has increased after the implementation of the house renovation and poverty alleviation program has increased.   Keywords: house renovation program, community welfare, and poverty alleviation